TINJAUAN KEPUASAN PASIEN TERHADAP PELAYANAN PENDAFTARAN ONLINE BERBASIS WHATSAPP DAN TELEPON PASIEN RAWAT JALAN DI RSU ANNA MEDIKA MADURA - M. Afif Rijal Husni; Nur Aini (program studi Rekam Medis dan Infomasi Kesehatan ITSK RS dr Soepraoen Malang, 2024)
At Anna Medika Madura's Hospital, patients still claim to be less content with online registration services with whatsapp online registration services and outpatient phones at Anna Medika Madura General Hospital. The type of research used was quantitative descriptive research. The population of this research were all the old outpatient who were online registration at Anna Medika Madura General Hospital and the determination of the number of samples using accidental sampling based on time using 5 dimension. Based on the results of the analysis on each dimension it be seen that of the 82 respondents, on the tangibles dimension expressed satisfaction with a percentage of 79,67%. On the reliability dimension, stated that they were very satisfied with a percentage of 80,63%. On the responsiveness dimension, stated that they were satisfied with a percentage of 76,26%. On the assurance dimension, stated that they were very satisfied with a percentage of 82,85%. On the empathy dimension, stated that they were very satisfied with a percentage of 81,71%. Thus the assurance dimension had the highest level of satisfaction. The average overall patient satisfaction is 80,22% in the satisfied category. The clarity and ease of the service are essential to improving the quality and level of the satisfaction of the patient, the quality of service having an effect on the patient’s satisfaction. Online registration can make it easier for the patient and is shown to be able to support hospital activities in the registration process and also to have the ability to reduce waiting times which will increase patient satisfaction.